Molecular and cellular mechanisms underlying postoperative paralytic ileus by various immune cell types - Sui, Chao; Tao, Liang; Bai, Chunhua; Shao, Lihua; Miao, Ji; Chen, Kai; Wang, Meng; Hu, Qiongyuan; Wang, Feng (Frontiers in Pharmacology, 2022)
Postoperative ileus (POI) is a well-known complication following gut manipulation or surgical trauma, leading to an impaired gut motility and prolonged postoperative recovery time. Few current therapeutic strategies can prevent POI, and this disorder remains to be a major clinical challenge for patients undergoing surgery. Comprehensive understanding of cellular and molecular mechanisms related to the pathogenesis of POI stimulates the discovery of more promising targets for treatment. POI is closely associated with a series of inflammatory events within the bowel wall and as key components of inflammatory mechanisms, different types of immune cells, including macrophages, dendritic cells, T lymphocyte, etc. play significant roles during development of POI. A variety of immune cells are recruited into the manipulation sites after surgery, contributing early inflammatory events or impaired gut motility. Our review intends to summarize the specific relationship between different immune cells and POI, mainly focusing on the relevant mechanisms underlying this disorder.